PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SARANA AIR BERSIH PERDESAAN DI DESA MALINO KECAMATAN BALAESANG KABUPATEN DONGGALA - Ahmad, Sulthan (Katalogis, 2013)
The purpose this research to analyze the society participation degrees into Malino Village of Balaesang District of Donggala Regency, and the factor which influence it. The data analizing that is used by qualitative, to measure the society participation degrees analized with using a likert skale. To know the factors which influence has been done by deep descriptive analyzing towards encourage of the society participation into the infrastucture of water clean management. The result of research indicates that the society participation degrees into Malino Village of Balaesang District of Donggala Regency about the infrastucture of water clean management is enough well, by participation degrees is medium. The factor that influence the participation society into the water clean management because there is mutual believes, and the society is asked to a role for every activity, so that the society feels obtaining a benefit from this activity and the village staff prepare to give an example, the constrain factor are instructure and the means which is developed not so support to wide development, there is no village regulation from the government related with the infrastucture of water clean management and the low participation of society to evaluate the problems related with the means of water clean management.